The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.jmedchem.6b01128
|View full text |Cite
|
Sign up to set email alerts
|

Sydnone Cycloaddition Route to Pyrazole-Based Analogs of Combretastatin A4

Abstract: The combretastatins are an important class of tubulin-binding agents. Of this family, a number of compounds are potent tumor Vascular Disrupting Agents (VDAs) and have shown promise in the clinic for cancer therapy. We have developed a modular synthetic route to combretastatin analogs based on a pyrazole core through highly-regioselective alkyne cycloaddition reactions of sydnones. These compounds show modest to high potency against human umbilical vein endothelial cell proliferation. Moreover, evidence is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…Instead, VDA effects on the microtubule cytoskeleton of endothelial cells (the primary target of VDAs) and subsequent changes in cell morphology are thought to be integral to their therapeutic efficacy . Indeed, recently, we have shown that assays using endothelial cells provided a good insight into the activity CA4 analogues that translated into in vivo efficacy …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, VDA effects on the microtubule cytoskeleton of endothelial cells (the primary target of VDAs) and subsequent changes in cell morphology are thought to be integral to their therapeutic efficacy . Indeed, recently, we have shown that assays using endothelial cells provided a good insight into the activity CA4 analogues that translated into in vivo efficacy …”
Section: Resultsmentioning
confidence: 99%
“…All compounds submitted for biological testing were recrystallised to consistent melting point and judged as >95 % pure by 1 H and 13 C NMR spectroscopy unless otherwise specified. Sydnones were prepared by standard methods (cyclodehydration of N ‐nitroso amino acid with trifluoroacetic anhydride) …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations